Industrial solvents - Garbelotto, Paulo (2009)
ndustrial solvents make up a group of indispensible products in the different segments of the production chain. Throughout the decades. their use has evolved with the increase in knowledge on the subject through scientific study and research and the development of new production technology and processes. leading to the increased field of application. This project. the result of the work of fourteen members from different areas at Rhodia. offers an update on the knowledge; gives its history and application throughout time; brings new technology and development; and points the way for growth in this product segment in the industrial market. The book. Industrial Solvents - Selection. Formulation. and Application. is a reference in technical literature dedicated to a specific field and is therefore required reading for all those interested in the evolution of this production segment